1993
DOI: 10.1007/bf01309668
|View full text |Cite
|
Sign up to set email alerts
|

Tissue tropisms of porcine parvovirus in swine

Abstract: Late-term gestation swine fetuses, similar to adult animals, are able to effectively mount immune response and survive porcine parvovirus (PPV) infection. An exception to this is the Kresse strain of PPV, which causes fetal death in late-term gestation swine fetuses. In an effort to understand the basis for this profound difference in pathogenicity between Kresse strain and the prototype strain of PPV, NADL-8, studies were designed to examine potential difference in sites of replication and quantity of virus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
2
24
1
1
Order By: Relevance
“…PPV also has extralymphoid targets, including pulmonary and renal epithelium, hepatocytes, and endothelium. 21 Although controversial, it has been proposed on the basis of in vitro and in vivo studies that observed differences in virulence among PPV isolates may relate to differences in tissue tropism. 6,16 Although similar studies have yet to be performed with PCV isolates, it appears, on the basis of immunohistochemical analyses of lesions in naturally and experimentally infected pigs, [1][2][3]10,12 that, compared with PCV 1, the recent isolates of PCV 2 have a wider tropism than just lymphoid tissue, which may account, in part, for its virulence in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPV also has extralymphoid targets, including pulmonary and renal epithelium, hepatocytes, and endothelium. 21 Although controversial, it has been proposed on the basis of in vitro and in vivo studies that observed differences in virulence among PPV isolates may relate to differences in tissue tropism. 6,16 Although similar studies have yet to be performed with PCV isolates, it appears, on the basis of immunohistochemical analyses of lesions in naturally and experimentally infected pigs, [1][2][3]10,12 that, compared with PCV 1, the recent isolates of PCV 2 have a wider tropism than just lymphoid tissue, which may account, in part, for its virulence in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Pigs with PMWS generally present with clinical signs and corresponding lesions at an age when maternal antibodies would be waning. 21 Pigs exposed to PPV at this time could be subclinically infected and transiently viremic prior to the development of immunity. 18 Although the pathogenesis of the newly described strains of PCV is not currently known, a similar scenario could also occur after infection of postweaning age pigs with this virus.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue tropism of PPV, replication in selective sites and quantity of virus produced may explain the distinction in pathogenesis. Viral antigen and viral DNA replication in the brain were demonstrated only in late-term fetal infection with the Kresse strain (Choi et al, 1987;Oraveerakul et al, 1993). In the present study, the replicative form of PPV genome was not demonstrated in tissue samples and PPV was not investigated in nervous tissue, but the viral genome was detected in many tissues, showing evidence of PPV spreading and tissue damage in transplacentally infected fetuses from vaccinated sows.…”
Section: Discussionmentioning
confidence: 64%
“…Differences in pathogenicity between PPV NADL-8 and Kresse strains in late-term gestation have been described, indicating the Kresse strain as more virulent (Choi et al, 1987;Oraveerakul et al, 1993). Comparing relative virulence of the same two prototype strains in experimentally infected porcine fetuses at immune competence age showed that the NADL-8 strain causes more fetal mortality (Lager et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…PPV is not regarded as a significant cause of mortality in postweaning and growing pigs, although PPV has an in vivo tropism for monocytes and lymphocytes. 3,18 PCV2 virion production in vivo is upregulated as a result of immune stimulation. 15 Because both PCV2 and PPV are DNA viruses and depend upon cellular DNA synthesis for optimal virion production, stimulation of host DNA synthesis by PPV could inadvertently promote PCV2 replication.…”
mentioning
confidence: 99%